A note on minimal envelopes of Douglas algebras, minimal support sets, and restricted Douglas algebras. (15th May 2001) - Guillory, Carroll
Abstract : We characterize the interpolating Blaschke products of finite type in terms of their support sets. We also give a sufficient condition on the restricted Douglas algebra of a support set that is invariant under the Bourgain map, and its minimal envelope is singly generated.